MicroRNA-140 Inhibits the Epithelial-Mesenchymal Transition and Metastasis in Colorectal Cancer - Jiazhi Li; Kun Zou; Lihui Yu; Wenyue Zhao; Ying Lu; Jun Mao; Bo Wang; Lu Wang; Shujun Fan; Bo Song; Lianhong Li (Elsevier, 2018)
MicroRNA-140, a cartilage-specific microRNA, has recently been implicated in the cancer progression. However, the comprehensive role of miR-140 in the invasion and metastasis of colorectal cancer (CRC) is still not fully understood. In this study, we confirmed that miR-140 downregulates SMAD family member 3 (Smad3), which is a key downstream effector of the TGF-β signaling pathway, at the translational level in the CRC cell lines. Ectopic expression of miR-140 inhibits the process of epithelial-mesenchymal transition (EMT), at least partially through targeting Smad3, and induces the suppression of migratory and invasive capacities of CRC cells in vitro. miR-140 also attenuates CRC cell proliferation possibly via downregulating Samd3. Furthermore, overexpression of miR-140 inhibits the tumor formation and metastasis of CRC in vivo, and silenced Smad3 has the similar effect. Additionally, miR-140 expression is decreased in the clinical primary CRC specimens and appears as a progressive reduction in the metastatic specimens, whereas Smad3 is overexpressed in the CRC samples. Taken together, our findings suggest that miR-140 might be a key suppressor of CRC progression and metastasis through inhibiting EMT process by targeting Smad3. miR-140 may represent a novel candidate for CRC treatment.